Effect of low-level laser therapy in wound healing of primary molar teeth extraction - Hazal Özer; Merve Abaklı İnci (BMC, 2024)
Abstract Introduction Tooth extraction in children requires attention to wound healing and pain management, which are influenced by patient-related factors and behavioral guidance. Aim of the study: The study aimed to evaluate the effect of LLLT on healing sockets in pediatric patients with bilateral primary molar teeth extraction and determine its impact on pain management. Methods 6-10 years of age, systemically healthy, and with atraumatic extraction indications of bilateral primary molar teeth were included in the study (n = 40). In the first session, randomly selected teeth were extracted under local anesthesia. In the control group, only clot formation in the socket was observed and photographed. The other group extractions were performed 2 weeks later. The low-level laser therapy (LLLT) group was treated with a 980 nm wavelength, in a continuous emission mode, 0.5 W power, 300 J of energy, 400 µm tip, 60 s diode laser and photographed. Nonepithelialized surface measurements were performed using ImageJ. Pain assessment was performed using the Wong-Baker Pain Scale. Statistical analyses were performed using SPSS software. Results There was a statistically significant difference between the groups in the Wong-Baker values in 3rd day (p < 0.05). In soft tissue healing on the 3rd and 7th day, the nonepithelialized surface of the laser socket was smaller than that of the control group, and the measurement results were found to be statistically significant (p < 0.05). Conclusion Although LLLT was not found to be very effective in reducing postoperative discomfort after extraction of primary molars, it provided better wound healing in extraction sockets.